Europe at a Crossroads: Failed Ideas, Fictional Facts, and Fatal Consequences - Thomasberger, Claus (Forum for Social Economics, 2015)
The crisis of the European Monetary Union has revealed the weakness and the fragility of the European integration process. The paper examines the institutional changes which are at the root of the instability. What are the driving forces behind the introduction of the euro? What role do theoretical considerations play in this process? What influence on European integration has been exerted by neoliberal beliefs and convictions? Relying on an approach that combines basic insights of Gunnar Myrdal with Karl Polanyi's idea of a "double movement," it concentrates on the institutional transformation that is at the basis of the European integration process. The relationship between (misleading) ideas and facts is at the center of the study. It examines the influence of ideas and theoretical models on European integration, the Single Market Program, the Maastricht process, the increasing imbalances since the introduction of the euro, and the strategies applied during the recent crisis.
Keywords: economic integration; financial aspects of economic integration; financial crises; international institutional arrangements

Toward a Sartrean Economics - Kail, Michel; Sobel, Richard (Rethinking Marxism, 2015)
Despite the absence of a systematic analysis of economics in Sartre's work, we argue that a Sartrean economics can indeed be said to exist, even if it is an economics that still awaits development. The status that Sartre accords to the concept of scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason but should be considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man's confrontation with a typically ungrateful nature but should rather be articulated through the concept of the world as elaborated in Sartrean philosophy.
Keywords: POLANYI, Karl, 1886-1964; SARTRE, Jean-Paul, 1905-1980; economic systems; economism; scarcity; world